(untitled) (Itinera, 2024)
Philosophical reflections on metaphor run throughout Western thought, from Aristotle to contemporary debates. Its Aristotelian definition, in fact, draws a picture that subsequent interpretations have taken up and either confirmed or overturned. Often, the lines of continuity have only been presumed, while supposed breaks ended up being more faithful to the original than intended. The aim of this essay is to start from Aristotle’s perspective on metaphor to highlight some of the most relevant stages in the history of this concept up to Friedrich Nietzsche: from the transformation of metaphor into a fundamental theme of rhetoric to the recovery of its cognitive function. In this sense, Nietzsche became a crucial turning point for 20th-century “metaphormania”.